Миф о Тифоне в первой Пифийской оде Пиндара (Pyth. 1, 15–28) и в Прометее прикованном (PV 351–372) [Viktoria Mousbahova: Typhos Myth in Pindar’s Pyth. 1. 15–28 and PV 351–372] - Мусбахова, В. Т. (Hyperboreus, 2026)
It has been agreed since long that the similarities between Typhos narrations in Pindar’s Pyth. 1. 15–28 and PV 351–372 suggest that they are not independent descriptions. But though the examination of their stylistics did not prove the dependence of one on another, the common opinion points to Pindar as the source for PV (on chronological grounds), with the exception of von Mess, who made a case for common epic source on which both poets drew. Griffith rejected von Mess’ hypothesis on the grounds that the supposed epic poem should have contained the aetiology of Aetna eruption (this is impossible according to Griffith in our lack of evidence about eruptions before 479 BC) and argued for Pyth. 1 as the source of PV. His reasons are not decisive and appeal once more to the accepted by many late date for PV. Besides that Griffith’s point requires us to believe that the aetiology of Aetna eruption could have been invented by one or another poet. But it is highly improbable that either Pindar or any other poet could invent the aetiology of volcanic eruption. There is a good deal of evidence including archaeologically proved data to suppose that the volcanic activity of Aetna, as well as that on the island of Pithecussae, was well known before the famous eruption of 479 BC. We may suppose the existence of oral tradition that linked volcanic activities with Typhos as a source for both poets without hypothesizing an epic poem on particular subject. The texts support this statement: Typhos was surely imagined by both authors as a fire-spitting monster (on the contrary in Theogony it is by Zeus’ thunderbolt that Typhos is burnt to ashes), but nowhere he is called πύρπνοος (Aesch. Se. 493, 511), though the detail should be of great importance for the newly invented aetiology of eruption. On the assumption that none of the poets was responsible for the aetiology and without adducing the theory of the third source the same selection of mythological stuff by the poets clearly points towards the dependence of one text upon the other. Their close examination resulted in following conclusions. 1. It has proved once more that the texts are stylistically independent and pursue two different scopes. The same event is seen by the authors from two contrary points of view, that of the victor and that of the vanquished. The author of PV refers to the eruption of Aetna so as to demonstrate the vulnerability of the power using brute force against its opponents. For Pindar the scale of the eruption itself, i.e. the force of subdued and imprisoned enemy, is to illustrate the mightiness of Zeus and the greatness of his victory. 2. The Typhos narrative in PV reveals close familiarity of its author with the volcanic characteristics of Aetna, namely with the fact that it is a constantly active volcano. From the time when Typhos was imprisoned beneath the mount it is Hephaestus that permanently works on its peaks. This present situation is denoted by the adverb νῦν which makes transition from past events of Typhomachia to the now of the natural phenomenon and has close parallel in Il. 24. 614–617 where it denotes the stage of Niobe myth when she is petrified. No such meaning can be adduced for the use of νῦν by Pindar. It seems rather preserved by the poet from his source where it introduced the aetiology of the eruption as a part of Typhos myth and corresponded to past events of Typhomachia. In PV νῦν is contrasted not only to the past of Typhos’ rebellion but also to the future of outburst of his anger (Aetna eruption). The eruption itself is described by means of a single metaphor of jaws of fire devouring rich soils of Sicily which may be compared to the story of Hephaestus’ struggle against Demeter for the possession of Sicily (Sim. Fr. 200 Bergk) routed in local mythology. 3. There is strict coincidence in compositional structure of both Typhos narrations (see the table on p. 25). In every case there is preamble in which the Typhos myth is introduced by ὅς as an exemplum of Zeus’ power seen from the two contrary viewpoints. The mythological description of Typhos that follows in PV naturally develops in the narration about his struggle against Zeus, while Pindar starts from its result (Pyth. 1. 15: ἐν αἰνᾷ Ταρτάρῳ κεῖται) exposing the characteristics of Typhos in the order reversed as compared both to that of PV (Pyth. 1. 15–17: θεῶν πολέμιος, ἑκατοντακάρανος, τὸν… Κιλίκιον θρέψεν… ἄντρον / PV 351–354: τὸν... Κιλικίων οἰκήτορα, ἑκατοντακάρανον, ἀντέστη θεοῖς) as well as to the chronological sequence of the events in the myth. The transition to the aetiology of volcanic activity is made by the adverb νῦν which in PV is marked out by the opposition to the past and future while in Pindar its only function is to introduce the main topic of narration. Finally, in both cases there is a conclusion for the aetiological part introduced by qualitative (τοιόνδε) or demonstrative (κεῖνο, related to the qualitative οἷον) pronoun emphasized by its position in the verse. These coincidences cannot be accidental, nor can be due to the third source, because the preamble and the conclusion of this type are not characteristic of epic narrative. Thus Pindar could compose his ode having in mind the Typhos description in PV and if we take inτο account the peremptory statement that introduces Pindar’s narrative (Pyth. 1. 13: ὅσσα δὲ μὴ πεφίληκε Ζεύς), he may have conceived it as a rivalry version of Prometheus’ myth which scoped to restore Zeus’s glory in its full greatness. So the date of PV should be put before 470 BC. Aeschylean Aetnaeae were performed on the occasion of foundation by Hieron of the new city of Aetna. The evidence of some Pindaric odes, prior to 470 BC, makes probable that it took place before this date and precludes us from accepting Mazon’s ‘economic’ supposition (to reduce Aeschylus’ visits to Sicily to two) that the Aetnaeae were performed on the same occasion as Pindar’s Pyth. 1. The fragments of the drama display some interesting similarities with PV: it had an episodic structure much more abrupt than that of PV, as in PV there was probably done some use of vaticinia ex eventu, and it dealt with local legendary stock closely associated with the volcano. If the drama was performed in 476 BC (Ἱέρωνoς τὴν Αἴτνην κτίζοντος) the Typhos narration in PV may reflect Aeschylus’ acquaintance with Sicily during his first visit to the island.